Blastocystis sp. Subtype Diversity in Wild Carnivore Species from Spain. (26th November 2019) - Calero‐Bernal, Rafael; Santín, Mónica; Maloney, Jenny G.; Martín‐Pérez, Manuel; Habela, Miguel A.; Fernández‐García, José L.; Figueiredo, Ana; Nájera, Fernando; Palacios, María J.; Mateo, Marta; Balseiro, Ana; Barral, Marta; et al.
Abstract: The occurrence and molecular diversity of the stramenopile eukaryote Blastocystis sp. was investigated by PCR and sequencing (Sanger and NGS) methods in 380 faecal specimens of free‐living carnivores in Spain. Blastocystis sp. was confirmed in 1.6% (6/380) of the specimens analysed. Two samples from a common genet and a fox were successfully subtyped as ST7 by Sanger. Using NGS, ST14 was found in a fox and a European polecat, ST7 in a fox, and two additional foxes presented mixed infections of ST1/ST2/ST4 and ST1/ST2/ST7, respectively. Wild carnivore species could act as carriers of zoonotic Blastocystis subtypes.